The influences of dormitory exercise on negative emotions among quarantined Chinese college students during the COVID-19 pandemic - Zhang, Yu; Wen, Zehui; Li, Junying; Shi, Yongbin; Meng, ShuQiao (Frontiers in Psychiatry, 2023)
This study explores the influences of different types of dormitory exercise on the negative emotions of quarantined Chinese college students during the COVID-19 pandemic. In a three-week intervention, participants self-selected into a rope skipping group (RSG), an aerobic exercise group (AEG), and a resistance exercise group (REG), while participants in the control group (CG) engaged, by choice, in no physical exercise. Exercise frequency was three times a week for 45 minutes, with an intensity of 60% 80% of maximum heart rate. Before and after the intervention, all participants completed the Self-rating Anxiety Scale (SAS) and the Self-rating Depression Scale (SDS). Student’s t-test was used for intra-group comparisons, while analysis of variance was used for inter-group comparisons. Within the three exercise groups, there were some differences in the decrease levels of anxiety and depression, statistically significant at (p<0.05); by contrast, the levels of anxiety and depression slightly increased in the CG group, again with statistical significance (p<0.05). Comparing each of the RSG, AEG, and REG with the CG, we found some statistically significant differences in decreasing levels of anxiety and depression (p<0.05). A comparison of the RSG and REG with the AEG also revealed some significant differences in levels of anxiety and depression (p<0.05). However, the RSG and REG did not significantly differ in levels of anxiety and depression (p>0.05). Long-term and strict dormitory quarantine led to different levels of anxiety and depression among quarantined college students. The three different types of medium-intensity dormitory exercise evidently decreased anxiety and depression levels of quarantined college students, but aerobic exercise had the greatest influence, while rope skipping and resistance exercise had equivalent effects.